2013
DOI: 10.1099/vir.0.047308-0
|View full text |Cite
|
Sign up to set email alerts
|

Tropism, compartmentalization and retention of banana bunchy top virus (Nanoviridae) in the aphid vector Pentalonia nigronervosa

Abstract: Plant viruses of the families Luteoviridae and Geminiviridae rely on hemipteran vectors for the infection of their hosts. Several lines of evidence have revealed that these viruses are transmitted by competent vectors in a circulative manner, involving entry into the vector's body and the crossing of epithelial tissues forming the alimentary tract and the salivary glands. Similar to luteovirids and geminiviruses, a third family of plant viruses, the family Nanoviridae, have also been reported to be transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…Figure 1 shows the average concentration of BBTV relative to the aphid actin gene in the gut, salivary glands, and haemolymph for the four aphid lineages fed from BBTV-infected banana plants for 4 or 10 days. Consistent with previous results [12], the relative amounts of BBTV seemed to be much greater in the gut tissues than in the salivary glands and haemolymph in all four lineages (Fig. 1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 1 shows the average concentration of BBTV relative to the aphid actin gene in the gut, salivary glands, and haemolymph for the four aphid lineages fed from BBTV-infected banana plants for 4 or 10 days. Consistent with previous results [12], the relative amounts of BBTV seemed to be much greater in the gut tissues than in the salivary glands and haemolymph in all four lineages (Fig. 1).…”
Section: Resultssupporting
confidence: 92%
“…Using immunofluorescence and immunocapture PCR procedures, we showed that BBTV antigens localize to the anterior midgut (AMG) and specific cells of the principal salivary glands (PSGs) [11]. In addition, we reported that BBTV rapidly translocates within the aphid vector; the viral particles first localize to the AMG, where they accumulate and are retained at higher concentrations than in either the haemolymph or the PSGs [12]. We have suggested two possible translocation paths; the first considers the movement of virions from the AMG to the PSGs through the haemolymph, while the second considers the direct translocation from the AMG to the PSGs because the tissues that form these organs can come into direct contact within the haemocoel [12].…”
Section: Introductionmentioning
confidence: 99%
“…One obvious possibility, although contrary to the current view of the nanovirus-aphid interaction, is that some or all FBNSV genome segments could replicate. Because the replication cycles of some double-stranded DNA (dsDNA) viruses can be completed within a few minutes (23), it is currently impossible to exclude a very early and transient phase of FBNSV replication that we cannot see under our experimental conditions and that previous investigations of nanovirus transmission (14,24) may have overlooked. The observation that the aphid-related genome formula adjusted very early with little further change at later time points (e.g., Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Most member species of the family Nanoviridae are aphid transmitted, and the viral form crossing gut and salivary gland barriers has been proposed to be the viral particles (11)(12)(13). Though nanovirus particles have never been directly visualized by electron microscopy inside the insect vector, studies using immunofluorescence against the coat protein of Banana bunchy top virus have consistently demonstrated that the virus accumulates within the aphid anterior midgut before being released into the hemolymph and translocated in the principal salivary glands (14). We have recently shown that each of the eight segments composing the genome of Faba bean necrotic stunt virus (FBNSV) reproducibly accumulates at a specific relative frequency within infected host plants, with the corresponding segment frequency pattern defining the "genome formula" (15).…”
Section: Importancementioning
confidence: 99%
“…Both methods of RT-PCR have been widely used to detect viruses in plants and insect vectors (Lett et al, 2002;Varga and James, 2005;Zhang et al, 2010Zhang et al, , 2013bWatanabe and Bressan, 2013;Wang et al, 2014a,b). In the present study, we sought to quantify two viruses over time in the various organs of their respective vector and nonvector insects using quantitative RT-PCR (RT-qPCR) and conventional RT-PCR.…”
Section: Introductionmentioning
confidence: 98%